2006
DOI: 10.1016/s0022-5347(05)00184-9
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Collecting System Diagnosed During the First 6 Years of Life After a First Urinary Tract Infection: A Study of 63 Children

Abstract: CDS were a common finding among children with UTI who had duplication anomalies. Although CDS and IDS were accompanied by VUR more often than were single systems, CDS were associated more often with severe VUR, other serious complications and poor renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 15 publications
2
46
0
4
Order By: Relevance
“…In all of our cases it was left open, with no adverse consequences. Since our patients did not have antenatal diagnosis, their medium age of treatment was 12 years, in contrast to that described in the literature (from six months to five years) (1,3,12,19). One of them had even been pregnant and had a normal delivery before duplex system with infrasphincteric ectopic ureter was diagnosed.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In all of our cases it was left open, with no adverse consequences. Since our patients did not have antenatal diagnosis, their medium age of treatment was 12 years, in contrast to that described in the literature (from six months to five years) (1,3,12,19). One of them had even been pregnant and had a normal delivery before duplex system with infrasphincteric ectopic ureter was diagnosed.…”
Section: Discussionmentioning
confidence: 63%
“…Pyeloureteral duplication or duplex system is one of the most common anomalies of the upper urinary tract (1). Embryologically, a complete duplex system arises from two separate ureteric buds and is more common in girls than boys, in a ratio of 6:1.…”
Section: Introductionmentioning
confidence: 99%
“…Out of 63 children having duplicated systems, they observed that duplicated system was present unilaterally in 81% and bilaterally in 19% of children. 8 Whitaker and Danks also found unilateral duplication more common than bilateral duplication (6:1). 9 Rege VM et al believed bifid ureter was more common in females and was found to be present often on the right side.…”
Section: Discussionmentioning
confidence: 93%
“…Otopsi bulgularında üst polün yüksek oranda displazik bulunması heminefrektomi uygulaması için dayanılan gerekçedir (25,31) . Bu nonfonksiyonel kısmın eksize edilmesi ile hipertansiyon, proteinüri ve malignansi gelişiminin engellenmesi amaçlanır (20) .…”
Section: Discussionunclassified
“…Heminefrektomi ile % 85 oranında kür sağlan-dığını bildiren çalışmalar mevcuttur (9) . Bu gibi olgularda alt üriner sistem cerrahisi gereksiniminin % 16 gibi düşük düzeyde olduğunu bildirenler çalışmalar olduğu gibi uzun dönem izlemlerinde % 64-70 oranında major alt sistem cerrahisi gerektiğini bildiren çalışmalar da vardır (5,10,20,22,31) . Yüzde 75 olguda alt pole reflü olduğu için nonfonksisyonel üst pol eksizyonunun yeterli olmayacağı kanısı yaygındır (13) .…”
Section: Discussionunclassified